Correlates of HIV infection in adolescent girls and young women in Lesotho: results from a population-based survey. Issue 9 (September 2019) - Low, Andrea; Thin, Kyaw; Davia, Stefania; Mantell, Joanne; Koto, Masebeo; McCracken, Stephen; Ramphalla, Puleng; Maile, Limpho; Ahmed, Nahima; Patel, Hetal; Parekh, Bharat; Fida, Neway; et al.
Summary: Background: HIV acquisition remains high among adolescent girls and young women (AGYW, aged 15–24 years) in sub-Saharan Africa. We aimed to estimate prevalence and incidence of HIV in AGYW and to identify correlates of HIV infection by using data from the Lesotho Population-based HIV Impact Assessment (LePHIA). Methods: LePHIA was a nationally representative survey of adults and children based on a multistage cluster sampling method with random selection of enumeration areas and households. All adults aged 15 years and older who had slept in the household the night before were eligible for participation; participants completed an interview and HIV testing. We estimated incidence with the HIV-1 limiting antigen avidity enzyme immunoassay combined with viral load and examined the association between demographic and behavioural variables (including characteristics of cohabitating mothers and sexual partners, when available) and prevalence and incidence among AGYW using logistic regression, incorporating survey weights. Findings: We interviewed 8824 households, including 2358 AGYW who were tested for HIV infection. Weighted HIV prevalence was 11·1% (95% CI 9·7–12·5) in the overall population (273 of 2358 AGYW), 5·7% (4·1–7·2) in adolescent girls aged 15–19 years (64 of 1156), and 16·7% (14·4–19·0) in women aged 20–24 years (209 of 1212). Annualised HIV incidence was 1·8% (0·8–2·8). Correlates of prevalent infection include reporting a history of anal sex (adjusted odds ratio [aOR] 3·08, 1·11–8·57), having lived outside Lesotho in the past year (1·86, 1·01–3·42), having a partner suspected or known to be HIV positive (11·7, 6·0–22·5), and having two or more lifetime sexual partners (1·84, 1·21–2·78, for 2–3 lifetime sexual partners; 2·44, 1·45–4·08, for ≥4 lifetime sexual partners). For the 570 AGYW living with their mothers, maternal education was negatively associated with HIV prevalence in their daughters (aOR 0·36, 0·15–0·82, per increase in level attended). For AGYW with a cohabitating partner, the factors associated with AGYW infection were partner age (OR 4·54, 1·30–15·80, for partners aged 35–49 years, although the OR was no longer significant when adjusted for HIV status of partner), HIV status (aOR 11·22, 4·05–31·05), lack of viral load suppression (OR 0·16, 0·04–0·66), and partner employment in the past year (aOR 3·41, 1·12–10·42). Interpretation: The findings confirm the importance of improving the treatment cascade in male partners and targeting preventive interventions to AGYW who are at increased risk. A regional approach to prevention could mitigate the effect of migration on transnational spread of HIV. Funding: President's Emergency Plan for AIDS Relief through the Centers for Disease Control and Prevention.